2007
DOI: 10.1002/ajmg.a.31812
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Latin European descent could be a requirement for association of NTDs andMTHFRvariant 677C > T: A meta‐analysis

Abstract: There are several studies that have found a positive association between neural tube defects (NTDs) and the common mutation 677C > T of 5,10-methylenetetrahydrofolate reductase (MTHFR), and others that have not found such an association. We updated the meta-analyses of the published data about NTDs and MTHFR 677C > T variant from January 1994 to October 2005 identifying 170 potentially relevant studies. After applying pertinent exclusion criteria, 37 different populations from 32 studies were included in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
32
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 54 publications
4
32
0
3
Order By: Relevance
“…Therefore, we performed a meta-analysis to assess the association between the C677T polymorphism and risk of bladder cancer. Our meta-analysis results indicated that the MTHFR C677T polymorphism was not associated with bladder cancer risk, which was consistent with the published meta-analysis data on other cancers in Caucasians [40,41]. However, we found an increased risk effect for 677T allele on risk of bladder cancer in Asians (our present study).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we performed a meta-analysis to assess the association between the C677T polymorphism and risk of bladder cancer. Our meta-analysis results indicated that the MTHFR C677T polymorphism was not associated with bladder cancer risk, which was consistent with the published meta-analysis data on other cancers in Caucasians [40,41]. However, we found an increased risk effect for 677T allele on risk of bladder cancer in Asians (our present study).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, folate-related genes widely investigated for their potential involvement in pathogenesis of NTDs. To date, several meta-analyses have been conducted to investigate the association between NTDs and SNPs for candidate genes involved in the folate pathway, including C677T and A1298C in the MTHFR (methylenetetrahydrofolate reductase) gene [37][39], A66G in the MTRR (methionine synthase reductase) gene [1], [39], A2756G in the MTR (methionine synthase) gene [39][41], and A80G in the RFC-1 (reduced folate carrier) gene [39], [42]. However, no meta-analysis has been conducted on the effect of the MTHFD1 genetic polymorphism on susceptibility to NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de estos estudios para la variante c.C677T, considerando trabajos que incluyeron principalmente poblaciones de origen caucásica, Van der Put et al 8 demostraron que dicho polimorfismo constituía un marcador de aumento de riesgo de manifestar DTN en todas las poblaciones analizadas, excepto para la italiana. Diez años después, Amorim et al 9 publicaron un meta-análisis considerando poblaciones de todos los orígenes étnicos. Estos autores, al igual que Van der Put el al 8 , confirmaron que la variante c.C677T era un factor de riesgo.…”
Section: Discussionunclassified
“…8 sociedad Pro ayuda del niño lisiado (teleton-chile). 9 En Chile, su prevalencia es de 0,5-0,8/1.000 nacimientos, de los cuales cerca del 50% corresponden a espina bífida (EB). Dentro de los pacientes con EB, la mayoría de ellos corresponden a mielomeningocele (MM) 2,3 .…”
unclassified
See 1 more Smart Citation